Feasibility study of emergency intervention for vascular injury outside the hospital. Issue 1 (December 2016) - Liang, Ming; Rong, Jing-Jing; Sun, Jing-Yang; Wang, Xiao-Zeng; Li, Fei; Wang, Geng; Liang, Yan-Chun; Han, Ya-Ling
Abstract Background Minimally invasive surgery in the field of traumatic vascular injury diagnosis and treatment has achieved good results. This study was designed to determine whether pre-hospital emergency intervention is feasible for vascular injury in a field intervention cabin under the condition of war or a disaster site. Methods Different types of animal experiments of vascular injury intervention were performed in a field intervention cabin. Treatment capacity was evaluated by data collection, including duration of surgery, clinical evaluation, image clarity, and equipment handling. Environmental adaptability and mobility were evaluated by maneuverability and long-distance mobility. Results A total of 56 surgeries (7 types) were performed in the field intervention cabin. Digital subtraction angiography (DSA) had good imaging performance. A total of 4800 km of long-distance mobility was performed, and all the equipment operated normally without any equipment failure. We participated in the medical service maneuver twice. The cabin unfolded and worked properly. There was no equipment damage during the medical service maneuver. Conclusions Use of a field intervention cabin under the conditions of war or disaster is feasible for pre-hospital emergency intervention of vascular injury.